The impact of managerial challenges on organisational performance :a case study of selected secondary schools on Mopani West Education District, Limpopo Province, South Africa - Lekoloane, Ngoako Wilson (My University, 2023)
The motivation for this study was to assess managerial threats that hinder the attainment of organisational goals in schools from the point of view of the school management teams. A qualitative study was conducted to assess the impact of managerial challenges on school performance. Data was collected through a standardised open-ended questionnaire using an in-depth interview technique and a focus group discussion. Two groups of respondents participated in the project. In-depth interviews were held with the first group of principals and a focus group discussion with the second group of deputy principals and departmental heads. The findings revealed that SMT members struggle with goal-setting and sometimes lack the innovation, capacity and understanding to set realistic and smart goals. There is a need for the empowerment of SMT’s to develop the requisite capacity to achieve at a higher level.
Thesis (MPAM.) -- University of Limpopo, 2023
Keywords: Organisational performance; Goal setting; Educational management; Strategic planning; School management team; School management and organization -- South Africa -- Limpopo; Organizational effectiveness; Performance -- Management; School management teams